Biosorption of Rare-Earth Elements From Aqueous Solutions Using Walnut Shell - Gallardo, Karem; Castillo, Rodrigo; Mancilla, Nikol; Remonsellez, Francisco (Frontiers in Chemical Engineering, 2020)
Agricultural wastes are considered as green adsorbents that can work as an alternative to recover critical and scarce metals from secondary sources. Critical elements as rare-earth elements (REEs) can be obtained from electronic wastes or tailings and could be recovered using these green alternatives. In this study, walnut shell (WS) was tested to determine whether several REEs can be efficiently retained by this green adsorbent. Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetry, and differential scanning calorimetry (TG-DSC) were used to characterize WS before and after REE adsorption. Analytical performance of REE quantification was evaluated, besides adsorption capacity and isotherms that were calculated in order to determine the model that fit well to REE adsorption. ICP-OES results indicated the lowest limit of detection and quantification (LOD and LOQ) with Eu (0.08 and 0.23 ppb, respectively); nevertheless, quantification of other elements was also at the ppb level. In order to obtain the highest adsorption of metals, 75- and 2,000-μm particle sizes were studied, reaching >80% of adsorption with both sizes. Additionally, several pH values were tested in order to determine the optimum condition for maximal adsorption and adsorption capacity, noticing that pH 4 showed the best adsorption percentage (>85%, qe = 6.5–8 mg/g). The Langmuir isotherm model fitted well for the Eu, La, Sm, and Gd adsorption equilibrium. Characterization of WS was done using FTIR, TG-DSC, and SEM. FTIR analysis showed several changes in the spectra after adsorption of REE tested, but major changes were observed at the OH group, which shifted up to 31 cm−1 of wavelength. Additionally, TG-DSC showed that WS pyrolysis was divided in three stages: vaporization of moisture (about 10% of weight loss); thermal decomposition of hemicellulose, cellulose, and lignin (higher than 60% of weight loss); and high-temperature calcination of residues (<25%). Finally, SEM characterization showed empty and filled pores of different sizes in WS after metal adsorption, and a more rugged aspect was observed. This study reveals that WS is an efficient low-cost adsorbent for REEs and can be used for future recovery of these elements from secondary sources.